PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS NEARPOD PADA MATERI TEKS LAPORAN HASIL OBSERVASI SISWA KELAS X SMAN 2 LUBUK PAKAM - Alfian, Apri; Rita, Rita; Kartika, Rika (BEST Journal (Biology Education, Sains and Technology), 2025)
This research is the process of developing and feasibility of interactive learning media based on nearpod on the observation report text material of class X students of SMAN 2 Lubuk Pakam. This study aimed to develop and test the feasibility and effectiveness of nearpod-based interactive learning media on the observation report text material for grade X students of SMAN 2 Lubuk Pakam. This type of research was RD (Research and Development). The procedure used in this research and development was the procedure from Sugiyono that was simplified from 10 to 7 stages, namely (1) Potential and problem stage, (2) Data collection stage, (3) Product design stage, (4) Design validation stage, and (5) Design revision stage (6) Product testing, (7) Final product. The population in this study consisted of all grade X students at SMAN 2 Lubuk Pakam during the 2024/2025 academic year, totaling 396 students, with a sample of 36 students. Based on the validation results by 2 material experts, it can be categorized as "feasible" with a percentage score of 76%. The assessment results by 2 media experts were categorized as "feasible" with a percentage result of 88.5%. The results of the feasibility test on Indonesian language teachers obtained an overall average of 87% categorized as "Very feasible" and the results of the feasibility test on students also gave a positive and good response with an average value of 79% with the category "feasible" and can be tested. The researcher tested the product individually and in small groups. The results of the individual test obtained a percentage of 82.8% and the small group test 82.5%, then from the results of the limited effectiveness trial, an average value of 81.1% was obtained with the category "effective”. Therefore, it was concluded that Nearpod-based interactive learning media on the observation report text material was feasible and effective for use as learning media